USM TO OFFER OFFSHORE PROGRAMME WITH MALAYSIAN NUCLEAR AGENCY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 30 May 2016 – The School of Physics (PPSF) Universiti Sains Malaysia (USM) would offer an offshore Master in Science (Radiation Science) degree programme with the Malaysian Nuclear Agency in Bangi beginning this September.